1998
DOI: 10.4315/0362-028x-61.9.1129
|View full text |Cite
|
Sign up to set email alerts
|

Thawed Cod Fillets Spoil Less Rapidly Than Unfrozen Fillets When Stored under Modified Atmosphere at 2°C

Abstract: The effect of two months of frozen storage at -20 degrees C on the spoilage characteristics and shelf life of thawed and modified atmosphere packed (MAP) cod fillets stored at 2 degrees C was studied. Thawed MAP cod fillets were compared with fresh cod fillets stored in CO2-containing modified atmospheres with and without added oxygen. The shelf life of 11 to 12 days in the fresh MAP cod was extended to more than 20 days in the thawed MAP cod at 2 degrees C. This shelf life extension was most likely due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 0 publications
8
44
0
1
Order By: Relevance
“…• C. 11 From the present result it is obvious that a similar conclusion holds for freeze-chilled fish.…”
Section: Chemical Analysessupporting
confidence: 70%
See 1 more Smart Citation
“…• C. 11 From the present result it is obvious that a similar conclusion holds for freeze-chilled fish.…”
Section: Chemical Analysessupporting
confidence: 70%
“…The drip loss was comparable to that reported for frozen-thawed MAP cod. 11 In rainbow trout, the lowest mean drip loss was observed on day 2 and the highest on day 12 (Table 4). The mean drip loss about doubled in rainbow trout during the storage period and the range was similar for both species.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…The advantages and disadvantages of 8 MAP have been periodically evaluated [1,2,3,4,5] and its use does not eliminate the 9 need for appropriate control of the storage conditions, especially temperature, as well as 10 an adequate protocol for food manipulation and sanitation at each preparation stage. There 11 have been many studies involving all food classes, raw [6,7], frozen [8,9], cooked, pre-12 cooked and prepared dishes [10,11]. These studies researched alternative methods to 13 promote the stability and safety of refrigerated food.…”
mentioning
confidence: 99%
“…Guldager et al (1998) reported that Pacific whiting fillet packed in 100% CO 2 and kept at 4°C has shelf life up to 15 days. Meanwhile, combination of MAP with super-chiling can extend the shelf life, i.e of Atlantic salmon (Salmo salar) fillets.…”
Section: Modified Atmosphere Packaging (Map)mentioning
confidence: 99%
“…It can be used alone or combined with other preservation technique like freeze-chilling which is able to extend the shelf life of pacific whiting, mackerel and salmon fillet (Fagan et and kept at 4°C has shelf life up to 15 days (Guldager et al, 1998).…”
Section: Map Application In Fresh Fishmentioning
confidence: 99%